Identification of salmon population bottlenecks from low flows in a hydro-regulated river. (October 2019) - Adeva-Bustos, Ana; Hedger, Richard David; Fjeldstad, Hans-Petter; Stickler, Morten; Alfredsen, Knut
Abstract: Flow regime alterations from hydropower regulation may impact fish populations. Impacts can be characterized using methods for mapping bottlenecks for different species life stages. Improving the understanding of such bottlenecks could provide a basis for mitigation measures. An integrated modelling approach coupling a salmon population model (IB-salmon), a hydraulic 1D model (HEC-RAS) and a temperature model (Air2Stream) was used to identify the bottlenecks constraining the salmon population in a hydro-regulated river (Ljungan River, Sweden). This integrated approach evaluated changes in the salmon population under different low flow scenarios, involving potential dewatering of spawning sites, and the effect of restored spawning sites. Model results demonstrated that low discharges in winter and summer were potential hydrological bottlenecks for the salmon population, particularly in winter due to potential dewatering of spawning sites. Restoration of spawning sites increased salmon production under all scenarios, posing a potential counter measure against low flows. Highlights: Salmon population constrains from low flows in a hydro-regulated river were studied. Smolt production changes were evaluated using an integrated modelling approach. Winter and summer low flows were potential bottlenecks for salmon production. Winter low flow was found the main constraint for Baltic salmon in River Ljungan. New spawning sites could mitigate low flows effects increasing smolt production.